Some Applications of New Complex Function Space Constructed by Different Weights and Exponents - Awad A. Bakery; Elsayed A. E. Mohamed (Journal of Mathematics)
In this article, we develop and study a new complex function space formed by varying the weights and exponents under a definite function. We investigate the geometric and topological characteristics of mapping ideals created using s-numbers and this complex function space. Also, the action of shift mappings on this complex function space has been discussed. Finally, we introduced an extension of Caristi’s fixed point theorem on it.